2015
DOI: 10.1016/j.plefa.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Enterocyte fatty acid-binding proteins (FABPs): Different functions of liver and intestinal FABPs in the intestine

Abstract: SUMMARY Fatty acid binding proteins (FABP) are highly abundant cytosolic proteins that are expressed in most mammalian tissues. In the intestinal enterocyte, both Liver- (LFABP; FABP1) and Intestinal-fatty acid binding proteins (IFABP; FABP2) are expressed. These proteins display high affinity binding for long chain fatty acids (FA) and other hydrophobic ligands, thus they are believed to be involved with uptake and trafficking of lipids in the intestine. In vitro studies have identified differences in ligand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
0
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(148 citation statements)
references
References 100 publications
3
131
0
14
Order By: Relevance
“…Intestinal Fatty Acid-Binding Protein 2 (i-FABP2) is mostly expressed in intestinal enterocytes [29], and studies have shown that i-FABP2 is an indicator of enterocyte damage and is associated with intestinal inflammation [30]. i-FABP2 is also involved in cell repair and proliferation [31,32] that may play crucial roles in immune responses to vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal Fatty Acid-Binding Protein 2 (i-FABP2) is mostly expressed in intestinal enterocytes [29], and studies have shown that i-FABP2 is an indicator of enterocyte damage and is associated with intestinal inflammation [30]. i-FABP2 is also involved in cell repair and proliferation [31,32] that may play crucial roles in immune responses to vaccines.…”
Section: Discussionmentioning
confidence: 99%
“…Axial patterning of FABP expression has been attributed to ligand and absorption specifi cities along the digestive track ( 58 ), but, in other cases, overlapping FABP expression sites and ligand binding specifi cities may represent a mechanism for ensuring functional redundancy. Studies directly comparing FABP1 -and FABP2 -null mice have revealed markedly different phenotypes, indicating that the encoded proteins indeed have different functions in the intestinal lipid metabolism and whole body energy homeostasis ( 13,63,64 ).…”
Section: Discussionmentioning
confidence: 99%
“…This intracellular transport protein could also be beta-carotene oxygenase 2 (BCO2), although it is apparently mainly located in mitochondria [44]. The intracellular βC transporter could also be a fatty acid binding protein (FABP), more likely liver FABP (L-FABP), which is also present in the intestine and which displays high-affinity binding for various hydrophobic ligands [45]. At this step, it is important to make clear that only a fraction of absorbed βC is metabolized in the enterocyte.…”
Section: Apical Uptake Intracellular Metabolism and Basolateral Smentioning
confidence: 99%